Reaching more farmers: Innovative approaches to scaling up climate-smart agriculture - Westermann, Olaf; Thornton, Philip K.; Förch, Wiebke (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The purpose of this working paper is to provide insight into how we can use novel approaches to scale up research findings on climate-smart agriculture (CSA) to meaningfully address the challenges of poverty and climate change. The approaches described include those based on value chains and private sector involvement, policy engagement, and information and communication technologies and agro-advisory services. The paper draws on 11 case studies to exemplify these new approaches to scaling up. These are synthesised using a simple conceptual framework that draws on a review of the most important challenges to scaling up. This provides the material for a discussion around how particular scaling up approaches can help to address some of the challenges of scaling up. The analysis offers insights into scaling approaches, challenges and some opportunities for scaling CSA practices and technologies. We conclude that multi-stakeholder platforms and policy making networks are key to effective upscaling, especially if paired with capacity enhancement, learning, and innovative approaches to support decision making of farmers. Projects that aim to intervene upstream at higher leverage points can be highly efficient and probably offer cost-effective dissemination strategies that reach across scales and include new and more diverse partnerships. However, these novel approaches still face challenges of promoting uptake, which remain contextualized and thus require a certain level of local engagement, while continuously paying attention to farmer’s needs and their own situations.